Fuzzy multi-criteria decision making model for subcontractor selection in international construction projects - Ulubeyli, Serdar; Kazaz, Aynur (Technological and Economic Development of Economy, 2016)
A general contractor’s ability to select proper subcontractors in foreign projects is a key competitive advantage. Toward this aim, a subcontractor selection model (CoSMo) was developed in this study. As a computational approach, the fuzzy sets method was employed because it can model human judgment by means of linguistic values, combining qualitative and quantitative decision criteria into an aggregate measure. Although the algorithm may be complex for easy acceptance by industrial practitioners, this disadvantage was minimized through a computer-supported system. In order to gain a better understanding of the current practice of CoSMo, a real world construction project was conducted. As a result, it was observed that CoSMo has high practical application and can be used as an advisory system by satisfying principal contractor’s requirements to reduce the risk involved in the selection of a subcontractor. Moreover, it gives an initial idea of how subcontractors perform on each decision criterion and allows the main contractor to understand the picture on the strong and weak points of each bidder and thereby to take conscious decisions.First published online: 10 Jun 2015